Bankruptcy Statement And The Law Consequences - Suwardi Suwardi; Widyawati Boediningsih (LPPM of NAROTAMA UNIVERSITY, 2018)
Problems bankruptcy it is important in gave a legal certainty related to wealth of company .The certainty applied with article 22 bankruptcy code who said that since decision statement of bankruptcy spoken each a lawsuit who carried out by third not going to be covered unless that thing it would bring terms of advantages wealth it self. It is also the act of bankruptcy winners give rights to creditors and parties that other concerned parties to ask for a request for the cancellation of over legal action a debtor.